Упростите выражение СРОЧНОООО!!!! [latex] \frac{2ab}{ a^{3}- b^{3} } + \frac{a-b}{ a^{2}+ab+ b^{2} }[/latex]
Упростите выражение СРОЧНОООО!!!!
[latex] \frac{2ab}{ a^{3}- b^{3} } + \frac{a-b}{ a^{2}+ab+ b^{2} }[/latex]
Ответ(ы) на вопрос:
2ab a-b 2ab+(a-b)(a-b) 2ab+(a-b)²
------------------------ + ----------------- = ------------------------ = -------------------- =
(a-b)( a²+ab+b²) a²+ab+b² (a-b)( a²+ab+b²) (a-b)( a²+ab+b²)
2ab+a²-2ab+b² a²+b² (a-b)(a+b) a+b
= ----------------------- = --------------------- = --------------------- = ----------------
(a-b)( a²+ab+b²) (a-b)( a²+ab+b²) (a-b)( a²+ab+b²) ( a²+ab+b²)
Не нашли ответ?
Похожие вопросы